The Practice Of Deligitimization Decisions Court Due to The Intersection Of Judicial Review in Indonesia - Supriyadi A Arief; Sofyan Piyo; Ramadhan Usman; Janwar Hippy; Irlan Puluhulawa (Journal of Law and Policy Transformation, 2024)
The Post-Decision Intersection Between the Supreme Court and the Constitutional Court in Indonesia. The Constitutional Court Decision No. 70/PUU-XXII/2024 and the Supreme Court Decision No. 23/P/HUM/2024, both addressing the age eligibility requirements for candidacy in the 2024 simultaneous regional elections, have reignited tensions between two branches of judicial power. This tension is further exacerbated by the decision of the House of Representatives (DPR), through a Working Committee meeting, to favor the Supreme Court’s ruling. This study aims to analyze the extent of the intersection between the Supreme Court (MA) and the Constitutional Court (MK) by examining their respective decisions. The analysis adopts a normative approach, relying on secondary data as the primary source, supported by statutory, case law, and conceptual approaches to address the core issues. The findings reveal that the overlap between the Supreme Court and the Constitutional Court in conducting judicial reviews of regulations has led to delegitimization between Supreme Court Decision No. 23/P/HUM/2024 and Constitutional Court Decision No. 70/PUU-XXII/2024. To address this issue, both courts must exercise judicial restraint, particularly regarding substantive matters with potential overlap between their jurisdictions. Such restraint is essential to prevent external parties or institutions from exploiting court decisions to advance their institutional agendas, thereby avoiding unnecessary institutional conflicts.